181k views
1 vote
3x+6=-3(2x+4)


Show your work

User RaYell
by
5.4k points

1 Answer

7 votes

Answer:


\boxed {x = -2}

Explanation:

Solve for the value of
x:


3x + 6 = -3(2x + 4)

-Use Distributive Property:


3x + 6 = -3(2x + 4)


3x + 6 = -6x - 12

-Take
6x and add it to
3x:


3x + 6 + 6x = -6x + 6x - 12


9x + 6 = -12

-Subtract both sides by
6:


9x + 6 - 6 = -12 - 6


9x = -18

-Divide both sides by
9:


(9x)/(9) = (-18)/(9)


\boxed {x = -2}

Therefore, the value of
x is
-2.

User SvinSimpe
by
5.3k points